PROVING INEQUALITIES USING THE LAGRANGE FUNCTION - Zaripov, Otabek; Umirzakov, Murodjon; Teshayeva, Madina (Innovative Development in Educational Activities, 2023)
Proving inequalities has a special place in the International Mathematical Olympiad. There are various methods of proving such inequalities, and this article presents a method of proving inequalities using the Lagrange function, which is simple and easy to use.